Environmental risk assessment of the DvSSJ1 dsRNA and the IPD072Aa protein to non-target organisms. Issue 1 (2nd January 2021) - Boeckman, Chad J.; Anderson, Jennifer A.; Linderblood, Christopher; Olson, Taylor; Roper, Jason; Sturtz, Kristine; Walker, Carl; Woods, Rachel
ABSTRACT: Event DP-Ø23211-2 (hereafter referred to as DP23211) maize expresses the DvSSJ1 double-stranded RNA (DvSSJ1 dsRNA) and the IPD072Aa protein, encoded by the ipd072Aa gene. DvSSJ1 dsRNA and the IPD072Aa protein each provide control of corn rootworms ( Diabrotica spp.) when expressed in plants. As part of the environmental risk assessment (ERA), the potential hazard to non-target organisms (NTOs) exposed to the DvSSJ1 dsRNA and the IPD072Aa protein expressed in DP23211 maize was assessed. Worst-case estimated environmental concentrations (EECs) for different NTO functional groups (pollinators and pollen feeders, soil dwelling detritivores, predators and parasitoids, aquatic detritivores, insectivorous birds, and wild mammals) were calculated using worst-case assumptions. Several factors that reduce exposure to NTOs under more realistic environmental conditions were applied, when needed to provide more environmentally relevant EECs. Laboratory bioassays were conducted to assess the activity of DvSSJ1 dsRNA or the IPD072Aa protein against selected surrogate species, and margins of exposure (MOEs) were calculated by comparing the Tier I hazard study results to worst-case or refined EECs. Based on specificity and MOE values, DvSSJ1 dsRNA and the IPD072Aa protein expressed in DP23211 maize are not expected to be harmful to NTO populations at environmentally relevant concentrations.